2022
DOI: 10.2147/ijgm.s355589
|View full text |Cite
|
Sign up to set email alerts
|

Estimating VO2peak in 18–90 Year-Old Adults: Development and Validation of the FitMáx©-Questionnaire

Abstract: Purpose Cardiorespiratory fitness (CRF) plays an essential role in health outcomes and quality of life. However, it is often not assessed nor estimated. Objective CRF assessment is costly, labour intensive and not widely available. Patient-reported outcome measures estimate CRF more cost-efficiently, but current questionnaires lack accuracy. The aim of this study is to develop a new self-reported questionnaire to estimate CRF. Materials and Methods The FitMáx©-questionn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…The DASI score of 33.8 was sensitive and specific to discriminate high-risk patients from those who were non-high-risk. The DASI was originally developed for the evaluation of patients with cardiovascular diseases, and, therefore, a significant correlation with peakVO 2 is well demonstrated in multiple cardiovascular cohorts, with the correlation coefficients ranging from 0.31 to 0.71 [19,[32][33][34][35][36]. Furthermore, the DASI score is associated with exercise capacity in patients with chronic obstructive pulmonary disease, patients with cancer, and patients undergoing general surgery [17,21,37].…”
Section: Discussionmentioning
confidence: 99%
“…The DASI score of 33.8 was sensitive and specific to discriminate high-risk patients from those who were non-high-risk. The DASI was originally developed for the evaluation of patients with cardiovascular diseases, and, therefore, a significant correlation with peakVO 2 is well demonstrated in multiple cardiovascular cohorts, with the correlation coefficients ranging from 0.31 to 0.71 [19,[32][33][34][35][36]. Furthermore, the DASI score is associated with exercise capacity in patients with chronic obstructive pulmonary disease, patients with cancer, and patients undergoing general surgery [17,21,37].…”
Section: Discussionmentioning
confidence: 99%
“…CPET will be used to determine the maximal exercise capacity and the peak workload, to support the prescription of a tailored exercise rehabilitation programme [ 42 , 43 ]. The effect of the intervention on maximal exercise capacity, defined as VO 2peak , will be evaluated with the validated FitMáx©-questionnaire at randomisation, and follow-up [ 44 ]. Furthermore, recovery of O 2 kinetics (τ-rec) after submaximal exercise will be assessed with a Constant-Load Exercise Test (CLET) at 50% of the peak workload at randomisation and follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, the FitMáx showed a strong intraclass correlation (ICC = 0.93) with CPET-VO 2peak , and acceptable bias (-0.24 with 95%-LoA − 9.23–8.75), in a heterogeneous group of 228 patients (with lung, cardiac and oncologic diseases) and athletes. The results for FitMáx were compared with DASI (ICC = 0.62, bias of 3.32 with 95%-LoA − 14.81–21.44) and VSAQ (ICC = 0.87, bias of 3.44 with 95%-LoA − 10.11–16.98) in the same population and showed better agreement with CPET-VO 2peak [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized the population specific agreement between CPET-VO 2peak and FitMáx-VO 2peak at T 0 to be moderate-to good, with an ICC of > 0.70 [ 17 19 ]; and the ICC between change over time in CPET-VO 2peak and FitMáx-VO 2peak to be between 0.40 and 0.60 [ 20 , 21 ]. Furthermore, the ability of the FitMáx to discriminate between participants who did or did not improve in aerobic capacity was expected to be moderate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation